Sustentabilidade dos solos: análise das contribuições de uma sequência didática contextualizada em uma escola do campo no município de Tuparendi, RS - Wiethölter, Patrícia Daiane Loebens Diel (2018)
This study deals with qualitative research, with descriptive and exploratory character, regarding the perceptions that students of the final series of an elementary school in the countryside have on soil sustainability. Through research-action, the experiment was conducted in the municipality of Tuparendi, State of Rio Grande do Sul, and examined if the students can relate these knowledge through daily practices, aiming at sustainability concepts and Agroecology. On these assumptions, the research aimed to answer the following question: what are the contributions of a contextualized didactic sequence and the perceptions of elementary school students about soil sustainability in a rural school? Interviews and questionnaires were held so that the students could exhibit their previous knowledge about the study of soils and its sustainable practices. Shortly thereafter, they were subjected to the field exit to recognize practices, conservationists or not, of soils. In this visit, photos were collected for further discussion work in the classroom and material production for the differentiation of practices that promote soil conservation and preservation. A field day was also held nos sustainable soil management, with the participation of the school community, in order to sensitize them about the importance of preservation of the main livelihood of family agriculture. In the end, the students were again subjected to evaluation questionnaires on the importance of the activities and their conception on soils and sustainability, to, then, compare the answers to the first applied questionnaire. Concluding the process, it was found that the students had a real understanding on soils sustainability through the study, with the practice developed in the school. Also, in the rural school, with the background of daily practices, learning was favored. In the same way, the study confirmed that the contextualized didactic sequence applied offered a differentiated vision of sustainability, implying in the awareness of people in order to transform their reality. It is extremely important, in this way, that we instigate, within schools and in the whole education in its most diverse modalities, to reflect on practices that conserve and preserve the natural elements, from their particularities to the whole greater. The soil sustainability, its correct practices of management, conservation and preservation are a small fraction of the greater sustainability, of thinking and taking care of the planet Earth. Through the action of its main protagonist, the human being, must occur the preservation of the different species, living and not living, as well as natural elements, considering economic, social, cultural aspects, among others, ensuring a fair way of life to the present and future generations.